The Study of Organizational Behavior on Fishery Manufacture Industries Employees Performances - Handaru, Agung Wahyu; Mardiyati, Umi (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2014)
The purpose of this study was to examine the employee performance of fish-based food processing industries in West Java, which driven by variables of organizational culture, job satisfaction and motivation. The fishing industry in Indonesia has resulted in huge foreign exchange. On the other hand, their products are still poor quality and do not meet export standard. This is likely due to low employee performance. The research object were employees of three fish-based food processing plants. The sample was selected by simple random sampling technique. This study revealed different results from previous studies, that only organizational culture has an effect on employee performance. While job satisfaction and motivation has no effect on performance.